2013
DOI: 10.1371/journal.pone.0075020
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Attachment Glycoprotein Genes of Human Respiratory Syncytial Virus Subgroups A and B in Children in Recent Five Consecutive Years

Abstract: Human respiratory syncytial virus (HRSV) outranks other viral agents as the cause of respiratory tract diseases in children worldwide. Molecular epidemiological study of the virus provides useful information for the development of globally effective vaccine. We investigated the circulating pattern and genetic variation in the attachment glycoprotein genes of HRSV in Beijing during 5 consecutive seasons from 2007 to 2012. Out of 19,942 tested specimens, 3,160 (15.8%) were HRSV antigen-positive. The incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
126
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(143 citation statements)
references
References 59 publications
14
126
1
2
Order By: Relevance
“…Based on its reaction with monoclonal antibodies against glycoprotein G and fusion protein F, RSV has two main genetic subtypes, A and B. There are 11 genotypes in subtype A (GA1-7, SAA1, ON1, and NA1-2) and 20 in subtype B (GB1-4, BA1-10, SAB1-4, and URU1-2) [12]. Although these subtypes can co-circulate, subtype A tends to be predominant, which might reflect time or geographical factors; virus circulation and evolution can be affected by several other factors including virus infectivity and spontaneous mutations as well as host group immunity [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on its reaction with monoclonal antibodies against glycoprotein G and fusion protein F, RSV has two main genetic subtypes, A and B. There are 11 genotypes in subtype A (GA1-7, SAA1, ON1, and NA1-2) and 20 in subtype B (GB1-4, BA1-10, SAB1-4, and URU1-2) [12]. Although these subtypes can co-circulate, subtype A tends to be predominant, which might reflect time or geographical factors; virus circulation and evolution can be affected by several other factors including virus infectivity and spontaneous mutations as well as host group immunity [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Although these subtypes can co-circulate, subtype A tends to be predominant, which might reflect time or geographical factors; virus circulation and evolution can be affected by several other factors including virus infectivity and spontaneous mutations as well as host group immunity [13,14]. Gender-related susceptibility to RSV infection, with male children reportedly more at risk than females, remains controversial [12]; however, comparatively higher percentages of respiratory infections are reported in women, which might be due to increased exposure to airborne infections through frequent contact with children and elderly family members.…”
Section: Introductionmentioning
confidence: 99%
“…By phylogenetic analyses for nucleotide sequences of HVR2, HRSV-A have been classified into 11 genotypes (GA1-GA5, GA6-GA7, SAA1, NA1-NA2 and ON1) and HRSV-B into 22 genotypes (GB1-GB4, BA1-BA6, BA7-BA10, BA-C, SAB1-SAB3, SAB4, URU1, URU2 and CB1) (Cui et al, 2013b). In 2003, Trento et al (2003 reported three new HRSV-B strains isolated in 1999, named BA genotype, with the characteristic of a major change in the HVR2 introduced by a duplication of 60 nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…The G protein is one of the targets of host immune response and thus a vaccine candidate. hRSV group B strains have been classified into 13 reported genotypes GB1, GB2, GB3, GB4, SAB1, SAB2, SAB3, SAB4, URU1, URU2, JAB1, CB1 and BA [5,8,9,21,23,25]. The BA genotype has 60 nucleotide duplication in the second hypervariable region of the G protein gene.…”
Section: Introductionmentioning
confidence: 99%